ANALYSIS OF ARCHETYPES THROUGH CHARACTER PORTRAYED IN MADELINE MILLER’S NOVEL CIRCE - Harianja, Sry Nency; Purba, Parlindungan; Syahputra, Fikry Prastya (Prologue: Journal on Language and Literature, 2024)
This study aims to analyze the archetypes that appear through the characters in Madeline Miller’s Circe. Archetypes are universal patterns that appear in stories, myths, and cultures that influence the way humans think, behave, and feel. The research method used is a qualitative method with an archetypical literary criticism approach. The research data is in the form of dialog quotes and narratives that describe the characters in the novel Circe. The data were analyzed by identifying the characteristics of the characters that correspond to certain archetypes, testing their suitability, and explaining the archetypical meaning contained in the characters. The results show that the novel Circe presents several prominent archetypes, such as the Mother Goddess, Hero, and Witch archetypes. The character of Circe, as the main character, depicts the archetypes of the Mother Goddess and the Sorceress that reflect the strength, independence, and ambiguity of women’s roles in Greek mythology. Meanwhile, the character also displays the archetype of a Hero who struggles to find self-identity and overcome challenges in her life journey. This research contributes to the understanding of the use of archetypes in contemporary literary works, and its implications for the representation of characters and themes raised in the story.